2014
DOI: 10.1111/cge.12364
|View full text |Cite
|
Sign up to set email alerts
|

A ‘cure’ for Down syndrome: what do parents want?

Abstract: Recent advancements in molecular genetics raise the possibility that therapeutics or a "cure" for Down syndrome (DS) may become available. However, there are no data regarding how parents of children with DS perceive the possibility of mitigating specific manifestations such as the intellectual disability (ID) associated with DS, or curing the condition entirely. To explore these issues, we distributed a questionnaire to members of the Lower Mainland Down Syndrome Society in British Columbia, Canada. Questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 39 publications
4
47
0
Order By: Relevance
“…Underscoring this priority, 61% of parents of children with DS indicated they would like to reverse the intellectual disability (ID) associated with DS (Inglis, Lohn, Austin, & Hippman, 2014). Caregivers increasingly seek alternatives on their own; a study found that 83% of families were currently using or had used complementary or alternative medicine to alleviate symptoms of DS (Prussing, Sobo, Walker, & Kurtin, 2005).…”
Section: Individuals With Ds Display Developmental Alterations In Bramentioning
confidence: 99%
“…Underscoring this priority, 61% of parents of children with DS indicated they would like to reverse the intellectual disability (ID) associated with DS (Inglis, Lohn, Austin, & Hippman, 2014). Caregivers increasingly seek alternatives on their own; a study found that 83% of families were currently using or had used complementary or alternative medicine to alleviate symptoms of DS (Prussing, Sobo, Walker, & Kurtin, 2005).…”
Section: Individuals With Ds Display Developmental Alterations In Bramentioning
confidence: 99%
“…The choice of parents is justified because their role to influence activities and intervention is well documented in literature (Inglis et al . ). Specifically, the present authors investigated the beliefs regarding facilitators and barriers of PA and sport as well as physical and psychological benefits.…”
Section: Introductionmentioning
confidence: 97%
“…As a direct consequence of the narrow design of this research, the targets of interventions are sometimes more controversial among patients and their families than those immersed in medical culture realize. For example, when parents of people with Down syndrome in Canada were asked if they felt researchers should be trying to find a cure for Down syndrome, only 43 percent said "yes" [26]. Some research advancements hailed by the media as possible "cures" might be met by resistance from some parents of those with Down syndrome, a phenomenon described by one journalist as "Down syndrome soul searching" [27].…”
Section: Consequences Of Medicine's Valuing Of Intellectual Abilitymentioning
confidence: 99%